2002
DOI: 10.1111/j.1365-2621.2002.tb08743.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Escherichia Coli O157:H7 During Storage of Yogurt at Different Temperatures

Abstract: The behavior of E. coli O157:H7 strains during the storage of plain live yogurt at 4, 8, 17, and 22 ºC was investigated. Lactic acid bacteria and pH were also studied. Linear regression analysis was carried out to obtain the specific death rate, the death rate and time of death. During the 1st 24 h, the pathogenic strains decreased slightly at 4 and 8 ºC. This decrease was greater at 17 ºC, and even greater at 22 ºC. E. coli O157:H7 was not detected after 312, 168, 28, and 16 h at 4, 8, 17, and 22 ºC, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 22 publications
2
30
0
1
Order By: Relevance
“…Our results are in accordance with those observed by Kasımoglu and Akgün (19) and Bachrouri et al (5) , who reported counts of E. coli O157:H7 increased about 1 log CFU mL -1 from initial inoculum during fermentation process. In the same context, Osaili et al (18) reported a large increase of E. coli O157:H7 count of 3.05 log CFU mL -1 during the fermentation process.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Our results are in accordance with those observed by Kasımoglu and Akgün (19) and Bachrouri et al (5) , who reported counts of E. coli O157:H7 increased about 1 log CFU mL -1 from initial inoculum during fermentation process. In the same context, Osaili et al (18) reported a large increase of E. coli O157:H7 count of 3.05 log CFU mL -1 during the fermentation process.…”
Section: Resultssupporting
confidence: 93%
“…Some researchers have studied the survival of E. coli O157:H7 in food systems, especially yogurt, and they have related the survival of the cells during fermentation process (5,18) . Our results suggested E. coli O157:H7 was able to grow despite the acidic environment developed and the bacterial competition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bachrouri et al (2002) observed that E. coli O157:H7 counts decreased by only 0.8 log 10 cfu/g in yoghurt stored at 4 C for 72 h, while in yoghurt stored at 22 C, they could not detect any bacteria after 16 h of challenge. Since commercial Amasi was refrigerated at 7 C for 24 h, survival of E. coli O157:H7 could have been enhanced by low temperature, compared to that in traditional Amasi, which was kept at ambient temperature throughout the 3-days of challenge.…”
Section: Enumeration and Characterization Of Microorganisms In Traditmentioning
confidence: 94%
“…Akdemir-Evrendilek 22 noticed that E. coli O157:H7 in the plain yoghurt, yoghurt drink and fresh-salted yoghurt inoculated with 10 6 -10 7 cfu/mL E. coli O157:H7, survived for 45 days at 4 and 22ºC. Bachrouri et al 34 studied the behavior of E. coli O157:H7 strains during the storage of plain live yoghurt at 4ºC. The researchers reported that E. coli O157:H7 counts decreased from 4.4 log cfu/g to 3.6 log cfu/g after 72 h and was not detected after 312 h. In these samples the pH values ranged from 3.94 to 4.11 during the storage.…”
Section: Discussionmentioning
confidence: 99%